Recent Development of Thermophotovoltaic System for Waste Heat Harvesting Application and Potential Implementation in Thermal Power Plant - Rashid W.E.S.W.A.; Ker P.J.; Jamaludin M.Z.B.; Gamel M.M.A.; Lee H.J.; Rahman N.B.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Conversion efficiency; Energy conservation; Energy dissipation; Energy harvesting; Fossil fuel power plants; Global warming; Temperature measurement; Thermoelectric power plants; Waste heat; Waste heat utilization; Energy scavenging; Power generation plants; Spectral filters; Thermal power plants; Thermophoto voltaic cells; Thermophotovoltaic systems; Thermophotovoltaics; Waste heat harvesting; Fossil fuels